Lurasidone uses and dosages in Spain: RETROLUR, a real-world retrospective analysis using artificial intelligence - Mora, Fernando; Gómez Sánchez-Lafuente, Carlos; De Iceta, Mariano; Roset, Carolina; Cárdenas, Antonio; Pérez, Daniel; Álvarez-Barón, Elena; Gabarda-Inat, Irene; , Savana Research Group (Frontiers in Psychiatry, 2025)
IntroductionLurasidone is used for schizophrenia and bipolar depression in many countries, yet there is a lack of existing literature about its use, efficacy, and safety in real life. We aimed to characterize lurasidone-treated patients by analyzing unstructured information in electronic health records (EHRs).MethodsThis was a multicenter, retrospective, observational, and descriptive study that used data extracted from EHRs of patients initiating treatment with lurasidone in four Spanish hospitals from September 2019 to March 2022. Stratification included primary diagnosis, antipsychotic therapy, and lurasidone dose. Natural language processing and machine learning were used to extract and analyze unstructured clinical data using SNOMED CT terminology. Sociodemographic, clinical, and treatment characteristics, as well as symptoms and potential adverse events as efficacy and safety outcomes, were evaluated at inclusion and during follow-up.ResultsAmong 2,374,218 patients attending the participating hospitals during the study period with 66,523,391 EHRs, 272 initiated lurasidone and were included. Median (Q1; Q3) age was 46 (37; 56) years, and 60.3% were female. Common comorbidities were hypertension (46.7%), dyslipidemia (44.5%), and diabetes (30.5%), and 87.1% had received a median of three antipsychotics before lurasidone, being olanzapine (52.9%) and quetiapine (45.2%) the most frequently used. During follow-up, 16.9% of the patients discontinued lurasidone, and few patients (<1.2%) reached high doses (111 and 148 mg/day). Lurasidone demonstrated effectiveness in reducing positive and negative symptoms, anxiety, depression, and suicidal ideation, with a marked reduction in most of the adverse events compared to the pre-lurasidone period.DiscussionLurasidone reduced positive and negative symptoms frequencies with a favorable safety profile, while low discontinuation rates suggest efficacy-tolerability balance, patient satisfaction, and acceptability. Our data reflect that in Spain lurasidone is used at low doses, limiting its beneficial effects according to clinical trials results.